2014
DOI: 10.5812/hepatmon.13625
|View full text |Cite
|
Sign up to set email alerts
|

Serum Levels of Anti-Hepatitis B Surface Antibody Among Vaccinated Population Aged 1 to 18 Years in Ahvaz City Southwest of Iran

Abstract: Background:The duration of protection following primary series vaccination against hepatitis B is unknown in children and adolescents. It has been shown that the level of anti-hepatitis B surface antigen antibodies (anti HBs Ab) declines over years after vaccination.Objectives:The aim of this study was to estimate the long-term immunity against hepatitis B virus infection among children and adolescents who had received a complete hepatitis B vaccination series during infancy.Patients and Methods:In a cross-sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
25
3
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 24 publications
10
25
3
1
Order By: Relevance
“…This is in accordance with previous studies of vaccinees who reported that, the antibody levels decrease with time, but breakthrough infections in vaccinated people are rare [West and Calandra, 1996;Banatvala and Van Damme, 2003]. Norouzirad et al [2014] found a significant negative correlation between anti-HBs levels and age (r ¼ À0.220, P ¼ 0.0001).…”
Section: Discussionsupporting
confidence: 92%
“…This is in accordance with previous studies of vaccinees who reported that, the antibody levels decrease with time, but breakthrough infections in vaccinated people are rare [West and Calandra, 1996;Banatvala and Van Damme, 2003]. Norouzirad et al [2014] found a significant negative correlation between anti-HBs levels and age (r ¼ À0.220, P ¼ 0.0001).…”
Section: Discussionsupporting
confidence: 92%
“…7 Five (6.8%) vaccinated medical students were anti-HBs negative or had titres < 10 mIU/mL, and thus can be considered non-responders to vaccination. 25 Alternatively these students could have responded initially and their anti-HBs levels could have declined with age, 25 but this wasn't evaluated in our study. In our study, anti-HBs were detected in 42.9% of subjects "vaccinated with single dose" ( Table 3).…”
Section: Discussionmentioning
confidence: 91%
“…The anti-HBs titer correlated to the frequency of IFN-γ-producing HBs-specific T cells. Reports show that HBs-specific T cell and antibody responses did not differ between vaccines and HBV-recovered patients3738. This finding suggests that greater levels of antibody production would lead to enhanced immunity, and that HCV infection may directly or indirectly influence HBV surface antibody production.…”
Section: Discussionmentioning
confidence: 92%